International Student Exchange Influence on an Indonesian EFL Student’s Speaking Confidence - Ningsih, Vitra Silvia; Nurfaidah, Sitti; Faridawati, Faridawati; Tanghal, Analiza B (Institut Agama Islam Negeri Kendari, 2025)
This autoethnographic study explores how participation in an international student exchange program in the Philippines influenced an Indonesian English as a Foreign Language (EFL) student’s confidence in speaking English. Drawing from the first author’s personal experiences during a semester at Nueva Ecija University of Science and Technology, the study reflects on the emotional, social, and academic challenges encountered, and the growth that resulted from immersion in an English-speaking environment. Through systematic self-reflection and narrative inquiry, the research reveals that supportive intercultural interactions, exposure to authentic language use, and constructive feedback from mentors played a significant role in enhancing the author’s communicative confidence. The findings highlight the transformative potential of international exchange programs in fostering self-efficacy and language development among EFL learners.